2015
DOI: 10.1021/acs.inorgchem.5b00159
|View full text |Cite
|
Sign up to set email alerts
|

Oxidovanadium(IV/V) Complexes as New Redox Mediators in Dye-Sensitized Solar Cells: A Combined Experimental and Theoretical Study

Abstract: Corrosiveness is one of the main drawbacks of using the iodide/triiodide redox couple in dye-sensitized solar cells (DSSCs). Alternative redox couples including transition metal complexes have been investigated where surprisingly high efficiencies for the conversion of solar to electrical energy have been achieved. In this paper, we examined the development of a DSSC using an electrolyte based on square pyramidal oxidovanadium(IV/V) complexes. The oxidovanadium(IV) complex (Ph4P)2[V(IV)O(hybeb)] was combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 92 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…The EPR parameters for the pydim and pydip derivative are similar to those of related mononuclear O=V IV complexes, , , and comparable dinuclear compounds with class I valence‐isolated [OV IV (μ‐O)V V O] units , , , , . Similar valence delocalized (class II or III) behavior as found for [V 2 O 3 (pyphen) 2 ] · – has been previously reported for the radical anionic complexes [(L)OV IV (µ‐O)V V O(LO] · – with tridentate ONO 2– ligands based on hydroxy phenoxy hydrazides,, , , salenes, carboxy‐salicylaldiminates, or azophenolates,, and also the [OV IV (μ‐O oxido )(μ‐O phen )V V O] · 2+ complexes containing pentadentate (N′NONN′) 3– 2,6‐bis(phenoxymethyl‐ N , N ‐dimethylaminomethyl)aminomethyl)‐phenolates,, or complexes [(L)OV IV (µ‐O)V V O(LO] · 3+ complexes containing neutral N′NN′ ligands of the 2,6‐bis[benzimidazol‐2′‐yl]pyridine or ‐amine type, tris(2‐pyridylmethyl)amine, or 1,4,7‐triazacyclononane derivatives …”
Section: Resultssupporting
confidence: 55%
“…The EPR parameters for the pydim and pydip derivative are similar to those of related mononuclear O=V IV complexes, , , and comparable dinuclear compounds with class I valence‐isolated [OV IV (μ‐O)V V O] units , , , , . Similar valence delocalized (class II or III) behavior as found for [V 2 O 3 (pyphen) 2 ] · – has been previously reported for the radical anionic complexes [(L)OV IV (µ‐O)V V O(LO] · – with tridentate ONO 2– ligands based on hydroxy phenoxy hydrazides,, , , salenes, carboxy‐salicylaldiminates, or azophenolates,, and also the [OV IV (μ‐O oxido )(μ‐O phen )V V O] · 2+ complexes containing pentadentate (N′NONN′) 3– 2,6‐bis(phenoxymethyl‐ N , N ‐dimethylaminomethyl)aminomethyl)‐phenolates,, or complexes [(L)OV IV (µ‐O)V V O(LO] · 3+ complexes containing neutral N′NN′ ligands of the 2,6‐bis[benzimidazol‐2′‐yl]pyridine or ‐amine type, tris(2‐pyridylmethyl)amine, or 1,4,7‐triazacyclononane derivatives …”
Section: Resultssupporting
confidence: 55%
“…Therefore, the low difference between TiO2 CB edge and the Fermi level of the mediator, results to a low UOC of the cell. [211]. For DSSCs with N719 as dye and Pt as CE, characteristic performance parameters of UOC = 0.66 V, jSC = 5.2 mA•cm −2 , and PCE = 2% under 1 sun Basic additives such as TBP were excluded from the electrolyte formulation since ESI mass spectra and X-ray structures confirmed that these manganese compounds are susceptible to ligand exchange with TBP to form trans-TBP substituted [Mn(acac) 2 TBP] + .…”
Section: Vanadium Mediatorsmentioning
confidence: 99%
“…Inorganic redox mediator such as iodide/triodide , manganaese(II/III) , and potassium ferricyanide are generally used in electricity generation. Oxidovanadium(IV/V) and cobalt(II)‐bis[2,6‐bis(1'‐butylbenzimidazole‐2‐yl)pyridine] are complex redox mediators . The structures of the mentioned redox mediators are presented in Fig.…”
Section: Common Redox Mediators and Metabolic Uncouplersmentioning
confidence: 99%
“…The main drawback of using triiodide in dye‐sensitized solar cells is the property of corrosiveness. Hence, the triiodide was replaced with oxidovanadium complex redox mediators because of their good electron exchange and transfer rate . In quantum dot‐sensitized solar cells with a redox potential of ∼0.51 V, Mn(II/III) complexes produce high voltages of 1 V. Low solubility prevented the redox mediators from sustaining high photocurrent due to mass transport limits.…”
Section: Application Of Redox Mediators In Environmental Researchmentioning
confidence: 99%